Standard specification for Pipe, Steel, Electric-Fusion (Arc)-Welded (Sizes NPS 16 and Over) (American Society for Testing and Materials, 2005)
This specification covers electric-fusion (arc)-welded straight seam or spiral seam steel pipe NPS 16 and over in diameter (inside or outside as specified by purchaser), with wall thicknesses up to 3⁄4 in. (19.0 mm), inclusive. Pipe having other dimensions may be furnished provided such pipe complies with all other requirements of this specification.